The role of the essential element boron in plant growth / a comprehensive overview of the sustainable environment during the period of irrigation and germination - Estabraq Mohammed Ati; Shahla hussien huno; Dr. Reyam Naji Ajmi; Dr. Huda Farooq Zaki (Peerian Journals Publishing, 2024)
This article dealt with a comprehensive study on the role of boron in plants, as boron is considered one of the most important essential mineral elements that nourish plants because of its role in controlling the degree of absorption of water from the soil and the movement of sugars within the plant to their storage places, in addition to its effect on the absorption of nitrogen, potassium and calcium, and its importance in the formation of plant hormones (auxins). It helps in the germination of pollen and the growth of germination tubes, and the plant’s need for it is greater during the flowering stage. Therefore, its importance in the formation of seeds and fruits becomes clear. Boron is usually present in the soil in limited quantities, as it is absorbed by plants in the form of borates an increase in calcium in the soil is considered one of the most important reasons for the occurrence of symptoms of boron deficiency on plants. There is a contradiction between these two elements, and the high ground water level and poor ventilation act as obstacle plant absorption of boron, main function of boron is to work on the elongation, development and division of cells, in addition to the formation of fruits, seeds, controlling the movement of sugars and the formation of hormones within plant tissues in order to achieve optimal growth
Keywords: Element boron; Plant growth; Sustainable environment; Irrigation and ermination